2020
DOI: 10.1111/trf.16157
|View full text |Cite
|
Sign up to set email alerts
|

Safety profile of high molecular weight polymerized hemoglobins

Abstract: Background Hemoglobin (Hb)‐based oxygen (O2) carriers (HBOCs) are being developed as alternatives to red blood cells and blood when these products are unavailable. Clinical trials of previous HBOC generations revealed side effects, including hypertension and vasoconstriction, that were not observed in preclinical studies. Large molecular weight (MW) polymerized bovine Hb (PolybHb) represents a new class of HBOC with promising results. We evaluated the safety profile of PolybHb after an exchange transfusion (ET… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“… 3 First-generation acellular chemically modified HBOCs were shown to entail statistically higher risks of myocardial infarction and death in the clinical trials, 4 , 5 which are presumably related to their small molecular sizes, high intrinsic affinities to nitric oxide, and their acellular structure, which collectively cause extravasation, vasoconstriction, hypertension, and oxidative lesion. 5 , 6 , 7 , 8 To mitigate such risks, we have developed hemoglobin vesicles (HbVs), which are cellular-structured HBOCs encapsulating a purified and concentrated Hb solution in PEGylated phospholipid vesicles (liposomes; mean particle diameter, 225-285 nm), shielding all the toxic effects of molecular hemoglobin by means of a lipid bilayer membrane and by mimicking erythrocytes ( Figure 1 A). 9 , 10 , 11 , 12 The efficacy of HbVs, when used as a resuscitative fluid, has been studied extensively using animal models.…”
mentioning
confidence: 99%
“… 3 First-generation acellular chemically modified HBOCs were shown to entail statistically higher risks of myocardial infarction and death in the clinical trials, 4 , 5 which are presumably related to their small molecular sizes, high intrinsic affinities to nitric oxide, and their acellular structure, which collectively cause extravasation, vasoconstriction, hypertension, and oxidative lesion. 5 , 6 , 7 , 8 To mitigate such risks, we have developed hemoglobin vesicles (HbVs), which are cellular-structured HBOCs encapsulating a purified and concentrated Hb solution in PEGylated phospholipid vesicles (liposomes; mean particle diameter, 225-285 nm), shielding all the toxic effects of molecular hemoglobin by means of a lipid bilayer membrane and by mimicking erythrocytes ( Figure 1 A). 9 , 10 , 11 , 12 The efficacy of HbVs, when used as a resuscitative fluid, has been studied extensively using animal models.…”
mentioning
confidence: 99%
“…Animals were euthanized for 2 h post‐transfusion to collect the blood, liver, heart, spleen, and kidneys for analysis. Organ tissue was processed for inflammatory and organ damage markers as previously described 28 using the kits and assays outlined in Table S1.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, we have developed and evaluated a high molecular weight (MW) polymerized human Hb (PolyhHb) as an alternative to blood. Increasing the MW of the PolyhHb appears to resolve the issues associated with vasoactivity, thus mitigating vasoconstriction and hypertension previously observed in earlier generations of HBOCs 13 , 14 . High MW PolyhHb has also been shown to be safer and well-tolerated at higher doses, and capable of preserving microvascular blood flow and increasing O 2 delivery with limited toxicity 13 , 14 .…”
Section: Introductionmentioning
confidence: 90%
“…Increasing the MW of the PolyhHb appears to resolve the issues associated with vasoactivity, thus mitigating vasoconstriction and hypertension previously observed in earlier generations of HBOCs 13 , 14 . High MW PolyhHb has also been shown to be safer and well-tolerated at higher doses, and capable of preserving microvascular blood flow and increasing O 2 delivery with limited toxicity 13 , 14 . Moreover, our most recent publication demonstrated that a high MW PolyhHb can restore hemodynamics to a similar degree as blood in a severe model of traumatic brain injury followed by HS in rats 15 .…”
Section: Introductionmentioning
confidence: 90%